2018
DOI: 10.32528/agribest.v2i2.1625
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Komparatif Usahatani Kentang Atlantik Dan Kentang Granola Di Kecamatan Sempol

Abstract: ABSTRAKKentang merupakan tanaman sayuran unggulan yang memiliki potensi untuk berkembang di Indonesia, maka tujuan penelitian ini adalah : (1) Menganalisis perbedaan biaya produksi antara usahatani kentang atlantik dan kentang granola. (2) Menganalisis perbedaan keuntungan antara usahatani kentang atlantik dan kentang granola, dan (3) Mengidentifikasi faktor-faktor yang mempengaruhi produksi usahatani kentang. Data yang digunakan adalah data primer dan sekunder. Data yang terkumpul di analisis menggunakan uji-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
1
7
0
5
Order By: Relevance
“…Farmers who grow Atlantic varieties of potatoes form a partnership with Indofood Ltd. and farmers were informed the price of seeds and selling prices of their harvests at the beginning of the collaboration. Similar to the atlantic variety, potato farmers in Sempol district studied by Juiwati et al (2018) will give special treatment to potato seeds by splitting the seedlings according to their shoots.…”
Section: Results and Discussion Potato Farming Performancementioning
confidence: 99%
See 3 more Smart Citations
“…Farmers who grow Atlantic varieties of potatoes form a partnership with Indofood Ltd. and farmers were informed the price of seeds and selling prices of their harvests at the beginning of the collaboration. Similar to the atlantic variety, potato farmers in Sempol district studied by Juiwati et al (2018) will give special treatment to potato seeds by splitting the seedlings according to their shoots.…”
Section: Results and Discussion Potato Farming Performancementioning
confidence: 99%
“…The results of statistical tests showed that there were significant differences in income and profits of the two varieties and showed that the farming of granola variety is more profitable. Juiwati et al (2018) in her research also showed that the cultivation of Granola potato in Sempol District was more profitable than the Atlantic variety. The results showed a difference in production costs, amounting to IDR 22,500,079 for granola varieties and IDR 22,146,941 for Atlantic varieties.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Biaya terbesar yaitu biaya bibit dengan persentase 37,58 % dan 44,95. Biaya variabel terbesar dalam pembelian bibit dengan persentase 34,21%-36,39% (Juiwati et al, 2018). Penerimaan dihitung dengan mengalikan jumlah produksi (satu musim/satu tahun) dengan harga jual persatuan kg.…”
Section: Metode Penelitianunclassified